Assessment of sports coaching patterns, physical abilities, and physical fitness in athletics: a study of the provincial sports week championship - Suratmin Suratmin; I Putu Darmayasa; Wigutomo Gozali; Qonita Awliya Hanif; Y Touvan Juni Samodra; Isti Dwi Puspita Wati; Didi Suryadi; BM. Wara Kushartanti; Ella Fauziah (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
The provincial sports week championship (PORPROV) organized by the Indonesian National Sports Committee (INSC) of Bali Province is held every two years followed by INSC Regency or City. Observing the results of each provincial sports week which became the first champion and runner up was always obtained by Badung and Denpasar regencies in a period of ten years. One of the contributors to a large number of medals is the athletic numbers of walking, running, jumping, and throwing as a measured sport. The Indonesian Athletics Association (PASI) of the districts or cities in Bali coaching patterns have not been evenly distributed as evidenced in the acquisition of medals at the provincial sports week, in addition to different coaching patterns supported by other facilities. Therefore, the purpose of the study was to examine the comparison of sports coaching patterns, physical abilities, and physical fitness of PASI athletic athletes at the Bali provincial sports week in 2022. This study uses a combination descriptive method (quantitative and qualitative), with a survey to find a comparison of the results of research data. The research sample was athletic athletes who participated in the Bali provincial sports week in 2022. The data were obtained through observations, interviews, questionnaires, tests and measurements, archives, and documentation. The data analysis used is data triangulation. The results of the study are (1) the creation of athletic sports coaching patterns and strategies through the management of district or city PASI administrators in Bali province to achieve achievement coaching goals, setting targets, and targets in developing and improving athletic sports achievements. (2) The level of physical ability of athletic sports athletes varies according to race numbers; fast walking numbers, running numbers, jumping numbers, and throwing numbers differ in physical needs and abilities. (3) The level of physical fitness of athletic sports number athletes according to the character of the race number, each race number requires different physical fitness. The results of the study make an expected contribution including overcoming obstacles, gaps, and obstacles faced by PASI district or city of Bali Province.